The role of real estate bank loans in addressing the housing crisis under the initiative of the Central Bank of Iraq for the period (2016-2021) (Entrepreneurship Journal for Finance and Business, 2023)
The problem of the housing sector is considered one of the most important problems that the Iraqi society has suffered from since the fifties of the last century, for several reasons, such as the large and rapid population increase that occurred in recent decades, and the accompanying large-scale migration from rural areas to city centers, and reasons related to the political, economic and security conditions.  In addition to the weakness of the financing system due to weak financing policies supporting housing, as the crisis increased due to the growing housing need, which is estimated at about (3) million housing units, so the Central Bank pursued an unconventional monetary policy to activate the real economic sectors, including the housing sector, in order to alleviate the severity of the crisis  housing in Iraq, and the Real Estate Bank has played a major role in providing real estate loans and alleviating the housing crisis under the initiative of the Central Bank of Iraq.